2017
DOI: 10.7717/peerj.3094
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of early dietary conditions and reproductive effort on the oxidative costs of reproduction

Abstract: The hypothesis that oxidative damage accumulation can mediate the trade-off between reproduction and lifespan has recently been questioned. However, in captive conditions, studies reporting no evidence in support of this hypothesis have usually provided easy access to food which may have mitigated the cost of reproduction. Here, I test the hypothesis that greater investment in reproduction should lead to oxidative damage accumulation and telomere loss in domestic zebra finches Taeniopygia guttata. Moreover, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Christe, Glaizot, Strepparava, Devevey, & Fumagalli, 2012), reproduction was found to have no effect on free-ranging female Soay sheep oxidative damage levels (Nussey, Pemberton, Pilkington, & Blount, 2009) and little effect in eastern chipmunks (Bergeron et al, 2011). In birds, several experimental studies demonstrate that reproduction does decrease oxidative resistance (Alonso-Alvarez et al, 2004;Wiersma, Selman, Speakman, & Verhulst, 2004) in a condition-dependent way (Noguera, 2017), leading to short-term mortality rather than a longterm change in longevity prospects (Alonso-Alvarez et al, 2006). This emphasizes the difficulty arising when trying to relate apparent CoR with the disposable soma theory (Monaghan et al, 2009).…”
Section: Is Condition Dependence Detectable At a Physiological Scale?mentioning
confidence: 99%
“…Christe, Glaizot, Strepparava, Devevey, & Fumagalli, 2012), reproduction was found to have no effect on free-ranging female Soay sheep oxidative damage levels (Nussey, Pemberton, Pilkington, & Blount, 2009) and little effect in eastern chipmunks (Bergeron et al, 2011). In birds, several experimental studies demonstrate that reproduction does decrease oxidative resistance (Alonso-Alvarez et al, 2004;Wiersma, Selman, Speakman, & Verhulst, 2004) in a condition-dependent way (Noguera, 2017), leading to short-term mortality rather than a longterm change in longevity prospects (Alonso-Alvarez et al, 2006). This emphasizes the difficulty arising when trying to relate apparent CoR with the disposable soma theory (Monaghan et al, 2009).…”
Section: Is Condition Dependence Detectable At a Physiological Scale?mentioning
confidence: 99%
“…Recently, oxidative stress has been suggested as a proximate mechanism that underlies variation in fitness related to breeding effort (Alonso-Alvarez, Bertrand, Faivre, & Sorci, 2007;Alonso-Alvarez et al, 2004;Bize, Devevey, Monaghan, Doligez, & Christe, 2008;Fletcher et al, 2012;Monaghan, Metcalfe, & Torres, 2009;Noguera, 2017;Stier, Reichert, Massemin, Bize, & Criscuolo, 2012). This proposition stems from the notion that when adults are reproducing, increased metabolism should lead to increased oxidative stress as a consequence of enhanced mitochondrial activity during ATP synthesis (Raha & Robinson, 2000).…”
mentioning
confidence: 99%
“…Reproduction, especially parental care, is energetically costly (Nilsson, 2002), can lead to oxidative DNA damage (Noguera, 2017) and potentially increased telomere loss (Heidinger et al, 2012;Reichert et al, 2014 Reproduction, especially parental care, is energetically costly (Nilsson, 2002), can lead to oxidative DNA damage (Noguera, 2017) and potentially increased telomere loss (Heidinger et al, 2012;Reichert et al, 2014 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our predictions, tropical and temperate stonechats had telomeres of similar length during their first breeding season and as adults. Reproduction, especially parental care, is energetically costly (Nilsson, 2002), can lead to oxidative DNA damage (Noguera, 2017) and potentially increased telomere loss (Heidinger et al, 2012;Reichert et al, 2014). Our previous comparative studies on hormone levels and mating behavior in tropical and temperate stonechats have shown that territorial aggression is accompanied by a peak in testosterone and corticosterone concentrations during nest-building in both temperate and tropical male stonechats (Apfelbeck, Helm, et al, 2017;Apfelbeck, Mortega, et al, 2017…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation